1989
DOI: 10.1002/chin.198903015
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Mechanistic Aspects of the Photooxidation of Water at the n‐TiO2/Aqueous Interface: Optically Induced Transients as a Kinetic Probe.

Abstract: ChemInform Abstract It is demonstrated that the method of optically induced photocurrent transients is a powerful tool for the study of the mechanisms of photoinduced charge transfer at the semiconductor/electrolyte interface. The results obtained for the (001) nTiO2/aqueous electrolyte interface suggest a model for water oxidation which involves two pH sensitive pathways. In the pH range 0-11, water oxidation appears to occur via an outer-sphere channel. From pH 12 to pH 15.5 (10 M NaOH) hydroxide oxidation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It has long been assumed that the water photooxidation reaction at the TiO 2 surface is initiated by oxidation of surface Ti–OH group (or OH – ions in an aqueous solution) by photogenerated holes, h + , by an electron-transfer mechanism. , Actually, the formation of • OH radicals in UV-irradiated TiO 2 systems was reported by a spin-trapping ESR , or low-temperature ESR method, diffuse reflection FTIR spectroscopy, and gas-phase emission spectroscopy . However, it was reported that the water photooxidation reaction at the TiO 2 surface did not produce any free • OH radicals but adsorbed • OH (or Ti–O • ) radicals, the latter of which gave ESR signals similar to those reported by the spin-trapping method.…”
mentioning
confidence: 99%
“…It has long been assumed that the water photooxidation reaction at the TiO 2 surface is initiated by oxidation of surface Ti–OH group (or OH – ions in an aqueous solution) by photogenerated holes, h + , by an electron-transfer mechanism. , Actually, the formation of • OH radicals in UV-irradiated TiO 2 systems was reported by a spin-trapping ESR , or low-temperature ESR method, diffuse reflection FTIR spectroscopy, and gas-phase emission spectroscopy . However, it was reported that the water photooxidation reaction at the TiO 2 surface did not produce any free • OH radicals but adsorbed • OH (or Ti–O • ) radicals, the latter of which gave ESR signals similar to those reported by the spin-trapping method.…”
mentioning
confidence: 99%